Evaluasi Keterlambatan Proyek Pembangunan Gedung Kantor Dinas Pekerjaan Umum Provinsi Riau - Doli Patumona; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Completion time determination project management, is among the first and the most important in the process of planning because it can be the basis of the whole planning. Project completion delay means overhead raise due to the elongation of construction time. it can inflict financial losses due to the possibility cost penalty of delays. The project of Regional Office of Civil Work Department is having a delay of 28 days from its contract duration. Final contract work at 80 weeks can only be fulfilled at 99,83% from 100% planned. Hence, the project is having a 0,17% delay. Project delay should be resolved by increasing the pace of construction on the remainingworks. Construction acceleration can be done by means of overtime work, equipment and workers addition, and shift system. The analysis conducted focuses on works that are on the critical path after the third addendum. From the analysis, it can be obtained that the cost due to delay stands at Rp.5.891.016.348,00. The cost that the contractor will spend by accelerating the works are Rp. 4.637.245.856,41 from overtime work alternative, Rp. 329.443.076,99 from equipment and workers addition alternative, and Rp. 1.713.439.777,73 from shift system alternative.Keywords: construction delay, construction cost, duration shortening, overtime work, equipment and workers addition, shift system.